Pengukuran Kadar Kromium Heksavalen (Cr (VI)) dan Fenol di Telaga Dusun Belahan Rejo Sebagai Pemantauan Kualitas Air di Kabupaten Gresik - Andini, Eka Andini San Putri; Zummah, Atiqoh; Teguh Pribadi, Eko; Safarina, Nourma (Chemistry Department, Universitas Islam Indonesia, 2024)
The decline in water quality is caused by increasing human activities. Likewise, human activities around the Belahan Rejo Hamlet lake affect water quality and can potentially reduce the quality of the lake water itself. This research was conducted to determine the levels of Hexavalent Chromium (Cr (VI)) and Phenol from the water of Belahan Rejo Hamlet Lake as monitoring and supervision to determine the condition of water quality. Analysis of Hexavalent Chromium (Cr (VI)) levels was carried out using UV-Vis Spectrophotometry referring to the SNI 6989.71: 2009 method and obtained an average value of 0.0148 mg/L, while Phenol levels were carried out using the HACH DR1900 Portable Vis Spectrophotometer referring to the DOC 316.53.01108 method and obtained a result of 0.018 mg/L. Based on the quality standards stipulated in Government Regulation of the Republic of Indonesia Number 22 of 2021 concerning the Implementation of Environmental Protection and Management, Appendix VI concerning the quality standards for Lake Water and the like, class 4, the quality standard for the Hexavalent Chromium (Cr (VI)) parameter is 1 mg/L and for the Phenol parameter is 0.02 mg/L. The levels of Hexavalent Chromium (Cr (VI)) and Phenol from this test are below the standard water quality limits, meaning that the lake water can still be used to irrigate crops and/or for other purposes that require the same water quality as these uses.